PENGARUH PENGGUNAAN MEDIA MANIPULATIF TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS III - Asnawati, Asnawati; Margiati, K.Y; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of using manipulative media on student learning outcomes in learning about the value of places to thousands in class III 64 Sungai Raya District Primary School in Kubu Raya District. The method used in this study is an experimental method with an experimental design Non Equivalent Control Group Desaign .. Based on the results of data analysis, the average experimental class Post Test was 76.37 and the control class average 69.10. Hypothesis test results using t-test obtained t count = 2.92 for dk = 52 and ? = 5% obtained t table of 2.02 which means thitung> t table (2.92> 2.02), then Ha is accepted. From the results of the effect size (ES) calculation, ES is obtained at 0.84 (high criteria). This means that the use of manipulative media has a big influence on the high student learning outcomes in mathematics learning in class III 64 Sungai Raya State Elementary School in Kubu Raya Regency.Keywords :  Manipulative Media, Student Learning, Mathematic Learning